Regulatory Implications of FMS for Voice Services in Turkey: Analysis of Recent Regulatory Acts on Deregulation and Margin Squeeze - Mehmet Bilal Ünver; Yavuz Göktaylar; Fatih Tezel (International Telecommunications Society (ITS), 2015)
FMS (fixed-to-mobile substitution) has increasingly been echoed within the regulatory agenda of the global and domestic policy actors as the usage of mobile telephony has rapidly exceeded that of the fixed telephony in the last decade. In this line of thinking and upon the drastic changes in market figures, e.g., diminishing fixed subscriber number and traffic, Information and Communication Technologies Authority (ICTA), regulatory authority in Turkey has had a survey carried out across the country in 2013, primarily to evaluate the degree of FMS. The survey results demonstrated the existence of one-sided (or imperfect) FMS, which has been found to influence fixed access and calling markets so as to ensure that these two markets are more competitive under a forward-looking approach. Moreover, ICTA has advanced the wholesale regulations within the context of fixed call origination market by imposing margin squeeze remedy on the fixed incumbent (SMP operator). While the latter step is criticized as being in conflict with the deregulation decision, the nature of the remedy being on ex post basis could be speculated to eliminate the concerns to an extent. Aggravating the discussion, an interesting development during the course of ICTA's intervention has happened in January 2015 when the SMP operator has increased its two retail prices so as to rearrange the margins. In this context, two questions arise from the discussions which extend to the philosophy of market regulation and deregulation: (i) First, does the regulator have a responsibility to pursue a regular (although being ex post) way of examining and when necessary intervening the incumbent's retail prices despite the fact Competition Authority has opened investigations several times on the same issue. (ii) Would the exposed degree of FMS have had a driving role for deregulation of fixed access and calling markets, which are freed from regulation including margin squeeze remedy on a different route across EU, i.e. mostly inner-market (or VOB-driven) developments towards effective competition. In this paper, such debates are addressed under the light of the reasons that justify margin squeeze as well as deregulation acts issued both by the Turkish regulator itself and in general way of regulatory understanding, i.e. with a particular emphasis to EU perspective and implementation. It is elaborated whether the underlined concerns relating to the degree of market regulation are successfully sorted out and translated into regulatory practice, specifically when thought with Turkey-centric competition problems, i.e. predominant WLR type service-based models, diminishing fixed markets. After discussions, it is found that although belatedly imposed and accompanied by deregulation, such a remedy would serve as a check-balance tool for a transition period, but not suffice to cover all the long-term problems by itself in cases where competing operators have insufficient competitive tools in terms of replicability. Last but not the least it is concluded that although European way of deregulation draws a differing roadmap, EU-centric pillars for regulation are implicitly injected into the Turkish system, which tries to resolve the issue with a trade-off together with the little possibility of ruling in a regulatory vacuum. Should this and a comparable risk of regulatory opportunism be prevented, a hybrid and promising example would be mentioned under the context of deregulatory reform.
Keywords: 330; margin squeeze; deregulation; FMS; EU regulatory framework; market definition; fixed; mobile; voice; Turkey